Navigating the Labyrinth of ESL: A Case Study on Linguistic Barriers and Autonomous Strategies among Indonesian English Education Students - Fadilah, Indah Nafsiyatul; Sakhiyya, Zulfa (Journey: Journal of English Language and Pedagogy, 2026)
This study investigates the barriers that English education students have when learning English as a second language (ESL) and the strategies they use to face their obstacles. The data were collected using a descriptive qualitative approach that employed a case study design. Researchers utilized semi-structured questionnaires and conducted in-depth interviews with English education students from Semarang State University. The participants were purposively selected from the sixth and eighth semesters, with seven students from each semester, as they had previously completed the course “Introduction to Second Language Acquisition (SLA)”. The conditions ensure that students have a good understanding  of the main theoretical concepts of second language acquisition. Students have may problems such as language-related problems (grammar, speaking, writing problems) and non-linguistic problems (anxiety, insecurity, fear of failure, and inconsistent motivation). Problems are compounded by distractions from the native language and lack of real language experience. To overcome these issues students employ various learning strategies such as self-study, targeted practice, social media engagement, vocabulary building, as well as the use of resources like translation apps, language learning platforms and AI chatbots. The results demonstrate that the successful ESL learning requires emotional control of academic behavior, learner independence and a positive social environment. The findings indicate that ESL acquisition is a complex process that should consider both linguistic and non-linguistic factors. The emphasis is on learning strategies, with psychological support and technology-enhanced learning.